Viable deletion mutant in the medium and large T-antigen-coding sequences of the polyoma virus genome. - Bendig, M M (1980)
A polyoma virus mutant that maps in the early region between the known hr-t and ts-a mutants has been isolated. Its 66-base-pair deletion results in structural changes in both medium and large T-antigens but causes no substantial alterations in viral replication or cell transformation.